Evaluation of the Use of Date Seed Flour in Feed on the Small Intestine Characteristics of Broiler - Ilmiatus Sholichatunnisa; Muhammad Halim Natsir; Tri Eko Susilorini; Danung Nur Adli; Osfar Sjofjan (Faculty of Animal Science, Universitas Brawijaya, 2022)
The purpose of this study was to determine and evaluate the use of date seed flour in feed on the small intestine characteristics of broilers. This study used 200 Day Old Chick (DOC) broilers with type MB 202. This study used a field experiment method with a Completely Randomized Design (CRD) consisting of 5 treatments and 4 replications. The treatments used were P0: basal feed without the use of date seed flour (DSF), P1: basal feed using 2.5% DSF, P2: basal feed using 5% DSF, P3: basal feed using 7.5% DSF, P4: basal feed using 10% DSF. The variables measured in this study were the number of villi, villi height, villi surface area, crypt depth, digesta pH, and digesta viscosity. The data obtained during the study were processed using Microsoft Excel software and analyzed using analysis of variance (ANOVA) and continued with Duncan's Multiple Range Test if the results obtained were significantly different (P<0.05) or very significantly different (P< 0.01). This study gave results that were not significantly different (P>0.05) on the number of villi, villi height, villi surface area, crypt depth, and digesta pH. However, this study was able to give very significantly different results (P<0.01) in digesta viscosity. The conclusion of this study is the use of date seed flour in feed up to 10% was able to give good results on the number of villi, villi height, villi surface area, crypt depth, and digesta pH of the small intestine of broilers, but it has not been able to give good results on the digesta viscosity of the small intestine of broilers.